2019
DOI: 10.1088/1674-1137/43/7/075101
|View full text |Cite
|
Sign up to set email alerts
|

Non-parametric reconstruction of dark energy and cosmic expansion from the Pantheon compilation of type Ia supernovae *

Abstract: The equation of state (EoS) of dark energy plays an important role in the evolution of the universe and arouses great interests in recent years. With the progress on observational technique, precise constraint on the EoS of dark energy becomes possible. In this paper, we reconstruct the EoS of dark energy and cosmic expansion using Gaussian processes (GP) from the most up-to-date Pantheon compilation of type Ia supernovae (SNe Ia), which consists of 1048 finely calibrated SNe Ia. The reconstructed EoS of dark … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 38 publications
4
12
0
Order By: Relevance
“…In particular, we have obtained Ω m0 = 0.253 +0.031 −0.027 and H 0 = 70.35 +2.49 −2.50 km s −1 Mpc −1 , which is in agreement with the recent estimate obtained H 0 = 70.5 +0.5 −0.5 km s −1 Mpc −1 in Ref. [53]. As mentioned in section IV, our detailed study shows that the deduced Hubble constant H 0 is approximately the mean value of the global and local measurements of H 0 , and thus alleviating the tension between these measurements.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In particular, we have obtained Ω m0 = 0.253 +0.031 −0.027 and H 0 = 70.35 +2.49 −2.50 km s −1 Mpc −1 , which is in agreement with the recent estimate obtained H 0 = 70.5 +0.5 −0.5 km s −1 Mpc −1 in Ref. [53]. As mentioned in section IV, our detailed study shows that the deduced Hubble constant H 0 is approximately the mean value of the global and local measurements of H 0 , and thus alleviating the tension between these measurements.…”
Section: Discussionsupporting
confidence: 93%
“…It has been observed that the value of Ω m0 obtained in this work is lower than the value obtained by the Planck analysis [55], which puts the limit on Ω m0 as Ω m0 = 0.315 ± 0.017 with 1σ errors [55]. Interestingly, it has been found that the best-fit value of the parameter H 0 obtained in the present analysis is almost same with the value H 0 = 70.5 +0.5 −0.5 km s −1 Mpc −1 , obtained by the Lin et al [53], using the Pantheon compilation of type Ia supernovae and the non-parametric method. On the other hand, it is well known that there is more than 3σ tension between the values of H 0 measured from the global CMB radiation (H 0 = 67.4 +0.5 −0.5 km s…”
Section: Results Of the Data Analysissupporting
confidence: 81%
“…[45][46][47][48][49][50][51][52]. Recently the non-parametric approach finds relevance in the reconstruction of kinematical quantities like the deceleration parameter q [53][54][55][56][57][58][59][60] and the jerk parameter j [61].…”
Section: Introductionmentioning
confidence: 99%
“…in Equation (14). Despite of this fact the FORTRAN code which derives the cosmological parameters produces a small difference in the results because the variables are evaluated in a different way.…”
Section: The Cardassian Cosmologymentioning
confidence: 99%
“…The availability of SN compilations allows testing old and new cosmological models. We select some of them among others: cosmological relativity in five spatial dimensions [9], an improvement of the Einstein-De Sitter cosmology [10], the ( ) f R gravity with additional logarithmic corrections [11] [12], influence of the detection of gravitational waves on a definitive theory of gravity [13], the derivation of the value of the Hubble constant as ( ) the dark energy cosmology [14] and the deduction of the parameters for Starobinsky gravity [15]. This paper reviews, in Section 2, old and new distance moduli in twelve cosmologies.…”
Section: Introductionmentioning
confidence: 99%